2016
DOI: 10.1021/acs.jpclett.6b00563
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Disulfide as a Protection Layer and Catalyst for Gallium Indium Phosphide Solar Water Splitting Photocathodes

Abstract: Gallium indium phosphide (GaInP2) is a semiconductor with promising optical and electronic properties for solar water splitting, but its surface stability is problematic as it undergoes significant chemical and electrochemical corrosion in aqueous electrolytes. Molybdenum disulfide (MoS2) nanomaterials are promising to both protect GaInP2 and to improve catalysis because MoS2 is resistant to corrosion and also possesses high activity for the hydrogen evolution reaction (HER). In this work, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 25 publications
5
93
0
Order By: Relevance
“…Increases in photoelectrode performance over the course of stability measurements have previously been observed for other MoS2 protected photocathodes and have been ascribed to the gradual exposure of additional MoS2 edge sites, 15,18 which are known to be the active sites for HER. 22 However, increasing the number of catalytic sites of the MoS2 catalyst should only increase reaction kinetics leading to an increase in the slope of the current-voltage curve and, perhaps its saturation photocurrent value.…”
Section: Introductionmentioning
confidence: 64%
“…Increases in photoelectrode performance over the course of stability measurements have previously been observed for other MoS2 protected photocathodes and have been ascribed to the gradual exposure of additional MoS2 edge sites, 15,18 which are known to be the active sites for HER. 22 However, increasing the number of catalytic sites of the MoS2 catalyst should only increase reaction kinetics leading to an increase in the slope of the current-voltage curve and, perhaps its saturation photocurrent value.…”
Section: Introductionmentioning
confidence: 64%
“…It is interesting to note that in this work no additional protective layer was deposited on n + p‐Si, and the MoS 2 layer offers dual functions as both an electrocatalyst and a passivation layer. Similar approach was also employed later on to couple MoS 2 with GaInP 2 /GaAs, which substantially improved the activity and stability of the photocathode.…”
Section: Strategies For Semiconductor/electrocatalyst Couplingmentioning
confidence: 99%
“…MoS 2 , as a semiconductor material, has attracted much attention because of its excellent properties for electrochemistry, optoelectrical applications, biosensors, and catalysis . Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…[17] MoS 2 ,a sasemiconductor material, has attracted much attention because of its excellent properties for electrochemistry, [18] optoelectrical applications, [19] biosensors, and catalysis. [20] Wang et al investigated the microwave absorption properties of MoS 2 and rGO, and found that the sample, which consisted of 10 wt %M oS 2 /rGO hybrid in paraffin, displayed am icrowave absorption bandwidth of 5.72 GHz at at hickness of 1.9 mm. [21] The maximumR Lr eached À50.9 dB at af requencyo f Reduced graphene oxide (rGO)@MoS 2 composites with al oose structurew ere prepared and added to poly(vinylidene fluoride) (PVDF) to form composites that showed superior microwave absorption and excellent electromagnetic interference shielding performances.…”
Section: Introductionmentioning
confidence: 99%